2020
DOI: 10.1002/aenm.202002464
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reconstruction and Phase Transition on Vanadium–Cobalt–Iron Trimetal Nitrides to Form Active Oxyhydroxide for Enhanced Electrocatalytic Water Oxidation

Abstract: However, the sluggish kinetics of oxygen evolution reaction (OER) in the electrolysis of water dramatically hinders its development for practical applications. [3] One of the challenges is to develop electrocatalysts with low-cost, abundance, high stability, and high catalytic activity for OER. Noble-metal oxides (such as IrO 2 and RuO 2) are most widely employed as efficient OER catalysts, but their scarcity and high cost limit their commercial application. [4] Therefore, tremendous efforts have been devoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 85 publications
2
136
0
Order By: Relevance
“…44 In addition, researchers have discovered that chalcogenides and phosphides containing two or more types of metals can also function as excellent OER ECs. [44][45][46][47][48][49][50][51][52][53][54] 2.1.3 Bifunctional compounds as electrocatalysts. While exploring new EC materials, researchers have identied various compounds that are highly-active for both HER and OER.…”
Section: Development Of Electrocatalyst Materialsmentioning
confidence: 99%
“…44 In addition, researchers have discovered that chalcogenides and phosphides containing two or more types of metals can also function as excellent OER ECs. [44][45][46][47][48][49][50][51][52][53][54] 2.1.3 Bifunctional compounds as electrocatalysts. While exploring new EC materials, researchers have identied various compounds that are highly-active for both HER and OER.…”
Section: Development Of Electrocatalyst Materialsmentioning
confidence: 99%
“…[260] Other dopants such as V, Mn, Cu, Ru, and Al are also available to boost the electrochemical performance of Fe/Co/Nibased (oxy)hydroxide catalysts. [54,77,[261][262][263][264][265] Particularly, the highvalence W is a structurally versatile dopant to modulate the electronic structure and optimize the intermediates adsorption for accelerating the OER kinetics. [36,176,266] Recently, Zhang et al reported the doping of several metal elements (i.e., W, Mo, Nb, Ta, and Re) in high oxidation states to modify the redox cycles of NiFe and FeCo oxyhydroxides.…”
Section: Nms For Oermentioning
confidence: 99%
“…Among various OER catalysts,3 dt ransition metal materials have been regarded as promising electrocatalysts in alkaline medium due to the formation of oxyhydroxide intermediates as favorable active sites for OER. [16][17][18][19][20][21] It is evident to identify the role of the surface reconstruction and termination, regulating the surface structure of the catalysts and the oxidation kinetics.M eanwhile,m etal supported catalysts offer ap romising approach to optimize the OER activity owe to the interfacial interaction of metals and the supports.Uptonow,noble metal oxides,such as iridium (Ir) and ruthenium (Ru) oxides,are the most superior catalysts for OER. [22] Alarge number of materials present enhanced OER performance by the decoration of metal clusters on the supported electrocatalysts,s uch as organic molecule, [23] carbon nanotubes, [24] metal oxides [25] and phosphides.…”
Section: Introductionmentioning
confidence: 99%